Violence Suffered by Christians, Jews, and Muslims Portrayed in Dan Brown’s Origin: Sociological Approach - Shafran, Mohammad Danial (English Department, Faculty of Humanities, Andalas University, 2024)
Religion is always interesting to discuss. Almost nothing is so intenselydiscussed from time to time other than discourse on religion. However, withthe development of technological and scientific advances, people began toshift their orientation to technology and science and leave religious beliefs.It is undeniable that as a result of this, religious people are discredited,isolated, and often become objects of violence, especially by atheists andliberalists. Origin by Dan Brown depicts many incidents and religiousviolence perpetrated by atheists and liberalists. The conflict betweenatheist and religious people makes the novel complicated and interested toread and study. The purpose of this study is to (1) determine the kinds ofviolence, and (2) to determine the causes of violence in the Origin by DanBrown. In conducting this study, the writer employs the violence theory byJohan Galtung and the analysis concept of violence causes by Moghadam.Moreover, the sociological approach is used as a knife to peel and findout the correlation between literary works and social life. The results ofthis study indicate that there are three types of violence depicted in thenovel, namely direct violence, structural violence, and cultural violence.In addition, the causes of violence in the novel are analyzed through threefactors: individual, organizational, and environmental factor. Finally,religious violence is behavior that must be eliminated from the earth.Violence essentially violates human nature as creatures that are createddifferently, whether the race, language, culture, and even religion.